INTEGRATION OF CRITICAL LITERACY IN ENGLISH LANGUAGE LEARNING AS A MEANS OF ENHANCING NATIONAL INTEGRATION IN THE SOCIAL CONTEXT OF INDONESIA - Saragih, Amrin (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2018)
Disintegration is now internally threatening Indonesia.  It is assumed that the problem is caused by cultural misunderstanding.  The cultural misunderstanding has resulted in intolerance and radicalism of group ideology.  For years Indonesia with its 250 million populations has been peacefully living together with Pancasila ideology in which unity in cultural diversities is highly appreciated and respected.  The root of problem lies in the practice of education and obviously the best solution is through education.  One of the solutions to the problem is by integrating critical literacy principles in the field of Englsih language learning.  Principles of critical multicultural and global literacy can be integrated in English language learning.  Theory of systemic functional linguistic (SFL) is in line with and contributes to the principles of critical literacy.  This paper combines principles of critical literacy and those of SFL in developing language learning materials.  It is expected that by integration of critical literacy principles and those of SFL in the practice of English language education, Indonesia can avoid disruptions of national disinttegration and regain national unity in harmony.